ANAK YATIM SEBAGAI OBJEK DAKWAH DALAM PERSPEKTIF AL-QUR’AN - Mardan Mahmuda (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Although there is an “yatim” term, “piatu” and “yatim piatu” term that developed in the midst of Indonesian society, still such understanding needs to be reviewed again. Because, in the literature of classical jurisprudence (fiqh klasik) and also in the Qur'an known term orphans (yatim) only. This scientific article is prepared using the literature study method. In order to know the Qur'anic view of orphan as the object of da'wah, the writer first searches the word orphan in Al-Qur'an by using Mu'jam Al-Qur'an by Muhammad Fuad 'Abd al-Baqiy. After that, the author describes in detail the orphan textually, then understands the context of the verses based on “asbab al-nuzul” and the “mufassir” opinion. Furthermore, the authors classify and conclude some matters relating to orphans as the object of da'wah contained in the Qur'an. Based on this, the author managed to reveal four things related to orphans namely; a) verses about orphans, b) classification of orphans as the object of da'wah perspectives of the Qur'an, c) social reality of orphans in the past in the Qur'an, d) da'wah approach to orphans perspective Al-Qur'an. Furthermore, this article is expected to be a contribution for da'wah practitioners, empowerment agencies, mosques officials and mushalla officials, religious institutions and other social institutions to maximize orphans maximally and sustainably.